Language Attitudes of Undergraduate Students towards English as a Social Identity - Sulistia Wati Razak; Mochtar Marhum; Anjar Kusuma Dewi; Jamiluddin Jamiluddin (Journal of English Language and Education, 2026)
English plays an important role not only as a means of communication but also as a symbol of social identity among university students. Although previous studies have reported generally positive attitudes toward English, limited attention has been given to how English functions as a social identity among English Education undergraduate students. This study aims to describe English Education undergraduate students’ language attitudes toward English as a social identity. A quantitative descriptive survey design was employed involving 25 sixth-semester students of the English Education Study Program at Tadulako University, selected through purposive sampling. Data were collected using a four-point Likert-scale questionnaire and analyzed through descriptive statistics. The findings reveal an overall very positive language attitude (M = 3.35), with the cognitive aspect obtaining the highest mean score, followed by the affective aspect, while the behavioral aspect remained positive but comparatively lower. The study concludes that English functions as an important symbolic resource in shaping English Education students’ academic and social identities, although its use in everyday communication remains relatively limited.